CuO coated olive cake nanocomposites for rapid phenol removal and effective discoloration of high strength olive mill wastewater - Yuney, Kivanc; Oladipo, Akeem Adeyemi; Gazi, Mustafa; Younis, Dilshad Zubair (Pergamon-Elsevier Science Ltd, 2020)
The potential of solid olive wastes-based adsorbent (CuO-OC) with photocatalytic power was established for the removal of total phenolics and photocatalytic discolourization of high strength olive mill wastewater (OMW). Clear insight of the FTIR and Brunauer-Emmett-Teller analyses showed that oxygen-containing functional groups of CuO-OC likely participated in the adsorption of total phenols from the OMW via a pi-pi interaction, hydrogen bonding and electrostatic interaction. Also, the total pore volume of CuO-OC decreased from 0.068 to 0.052 cm(3) g(-1) after adsorption, which suggested that phenolics were trapped within the micro- and mesopores of CuO-OC. The adsorption kinetics revealed that similar to 82.7-95% of the phenolic compounds were removed within the first 360 min which is relatively faster than adsorbents and methods reported elsewhere. The isotherm results showed that Redlich -Peterson equation fit the experimental data very well with least error (chi(2) = 1.46-3.19) and high correlation coefficients (0.992-0.996), which suggested a mixture of hetero- and monolayer coverage of the phenolics on the CuO-OC surface. Results obtained herein are of practical interest and the reuse efficiency of CuO-OC remained similar to 60% after 5 successive recycling. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Olive mill wastewater; Reuse olive wastes; Phenolics removal; Discoloration kinetics; CuO photocatalysis